The Relationship Between Adolescents' Knowledge Level About Reproductive Health And Their Behaviors To Prevent Sexually Transmitted Infections - Sara Surya; Rezqiqah Aulia Rahmat; Andi Kamal M. Sallo (International Journal of Health Sciences, 2026)
ABSTRACT Sexually Transmitted Infections (STIs) are a common health problem among adolescents due to a lack of knowledge and sub optimal preventive behavior. This study aims to analyze the relationship between adolescents' knowledge of reproductive health and their STI prevention behavior. The research method used a quantitative approach with a cross-sectional design with 150 adolescent respondents. Data were collected using a questionnaire and analyzed using chi-square and t-tests. The results showed that adolescents with a good level of knowledge had better preventive behavior (p<0.05). It was concluded that there is a significant relationship between knowledge and STI prevention behavior.